New record of spot-tail sleeper ray Narke dipterygia (Bloch and Schneider, 1801) (Elasmobranchii, Torpediniformes, Narkidae) from the coast of Gujarat, India - Dhaval Bhatt; Santosh Kumar Singh; Pradeep C. Mankodi (Journal of Fisheries, 2022)
Narke dipterygia (Bloch and Schneider, 1801), commonly known as numb ray, is a widely distributed species in the Arabian Sea and South-East Asian countries. It has been recorded from Oman, Pakistan, Sri Lanka, Malaysia, Singapore, Indonesia, Thailand, Viet Nam, China, Taiwan Province of China and Japan. In India, majority of the findings of the species is from east and west coasts of India, only two records were reported namely Bombay of Maharashtra and Kerala. The present paper confirms the presence of N. dipterygia for the first time from Gujarat coast located on the west coast of India. The diagnostic characteristics and remarks on the taxonomy and distribution of N. dipterygia have been described in this paper.